Pertumbuhan Semai Bakau Putih (Bruguiera cylindrica (L.) BI.) Pada Tingkat Salinitas Yang Berbeda - Elvi Rusmiyanto Pancaning Wardoyo,, Yusniawati, Mukarlina, (Jurnal Protobiont, 2017)
Salinity increase may effect the growths of several plants, for example (Bruguiera cylindrica (L.) BI.). This research aims to identify the growth of white mangrove seedling (B. cylindrica) on different salinity levels. Additionally, it attempts to recognise salinity that could be tolerated by white mangrove seedling (B. cylindrica). This research was conducted since Oktober to December 2016. It used Completely Randomised Design (RAL) consisting of six (6) treatments, namely control, NaCl 2,5% (S1) treatment, 3% (S2) treatment, 3,5% (S3) treatment, 4% (S4) treatment and 4,5% (S5) treatment. The result showed that NaCl treatments gave a clear effect toward seedling heights, leaf area, root lengths, wet crown weights,dry crown and root weights and chlorophyll content. However, such treatments appeared not to give an effect toward wet root weights. NaCl treatments started to effect growths with the fall of seedling heights, leaf area and root lengths at concentration of 3% and at 4% toward wet crown weights and dry crown and root weights. Meanwhile, the effect toward chlorophyll content was at concentration of 4,5%. Salinity which could be tolerated by B. cylindrica growth stood around 2,5% (25‰) – 3,5% (35‰) and 4% (40‰) for chlorophyll content.